Análisis de factibilidad del uso de redes SDN Omada en la Universidad Técnica de Babahoyo. - Rebolledo Gil, Nayeli Julissa (2024)
The case study focuses on performing a feasibility analysis to improve the networks in the IT department of the Technical University of Babahoyo, we are going to propose the Omada SDN networks within the Technical University of Babahoyo the infrastructure improvements were created as a important aspect to guarantee an optimal user experience in a constantly evolving technological environment. Nowadays, network connectivity is critical to the operational efficiency of Babahoyo Technical University, the use of Omada Software Defined Networking (SDN) emerges as a promising solution to overcome network management and performance challenges. The Omada SDN network offers a centralized and programmable architecture that allows dynamic and automated network configuration, optimizing the operational efficiency and functioning of the networks of the students and administrative staff of the Babahoyo technical university.